(untitled) (The South East European Journal of Economics and Business, 2021)
The paper contributes to the understanding of entrepreneurial activity by assessing the relative importance of eight entrepreneurial readiness factors across countries in different regions and stages of economic development. Drawing on the literature, this paper identifies eight principle national entrepreneurial readiness factors (NERFs) as (1) business freedom; (2) investment freedom; (3) investor protection; (4) property rights protection; (5) technological readiness; (6) innovation; (7) freedom from corruption; and (8) access to risk capital. NERF country data is subjected to a linear regression analysis for each factor’s influence on the sum of all eight factors which is called a country’s National Entrepreneurial Readiness Value (NERV). Six South East European countries, eight South American countries, ten South East Asian countries, and six West African countries are compared against one another and the benchmark of the four largest G7 economies. Results of this analysis are presented and show that investor protection, property rights protection, and freedom from corruption are the most impactful entrepreneurial readiness factors. These findings present future research implications of how these results link to endowments and relate to improving entrepreneurial readiness.